COLLECTIVE MEMORY “JUM’AT KELABU” DI BANJARMASIN (PERSPEKTIF RESOLUSI KONFLIK ATAS PERISTIWA 23 MAY 1997) - Husnul Khotimah (Pascasarjana UIN ANTASARI Banjarmasin, 2017)
This paper intends to explore the events of the conflict on 23 May 1997 from the aspect of the peaceful resolution. Where a peace-building effort is needed to maintain a peaceful situation. With the collective memory being represented in the present mass, it is part of the form of efforts in fostering post-conflict sustainable peace. Through the elements of society (Non-Governmental Actor) the memory of conflict is represented in the public sphere as a form of warning against forgetting over history.The role of a non-governmental actor in peacebuilding has a strategic role in resolving conflicts and building peace post-conflict. There are three things raised in this research that is: The incident of conflict